Determination of Trace Metals by Differential Pulse Voltammetry at Chitosan Modified Electrodes - Martínez-Huitle,C.A. (2010)
Surface modification by chitosan (CT) on a glassy carbon electrode (GCE) was employed in the present study to determine metal traces (Cu, Pb, Cd, Co, As and Pt). Previous report about the chitosan film affinity toward positive or negative species demonstrated and allowed the application of these polymeric films for detecting heavy metals in aqueous solutions. The modified surface exhibited an affinity to chelating metal ions in solution, forming complexes. Differential pulse voltammetry combined with a pre-concentrating process and standard addition method were employed for trace analysis, obtaining the detection ranges (Cu (II) from 3.99´10-6 to 3.91´10-5 mol L-1, Pb(II) from 1.99´10-6 to 1.58´10-5 mol L-1, Cd(II) from 1.59´10-5 to 6.23´10-5 mol L-1, As(IV) from 7.99´10-6 to 5.04´10-5 mol L-1, Pt(IV) from 8.19´10-6 to 3.59´10-5 mol L-1, Co(II) from 6.11´10-4 to 2.78´10-3 mol L-1), calibrations plots and relevant equations for each metal. Finally, cyclic voltammetry technique was used to characterize the polymeric surface behavior in presence of different metals and during the differential pulse voltammetric analysis. The results are described and discussed in the light of the existing literature.